Main factors of primary arterial hypertension development and pathogenesis in young, call-up-aged men with complicated family anamnesis - V. A. Lusov; E. M. Evsikov; Yu. M. Mashukova; T. V. Kotov; N. O. Kugaenko; N. E. Ivakhnenko; T. B. Salova (Российский кардиологический журнал)
To identify the role of cardiovascular pathology, renal, renovascular and renourinal anomalies, neurogenic and endocrine diseases in arterial hypertension (AH) pathogenesis among young, call-up-aged men hospitalized for examination and primary AH diagnosis verification, 60 men aged 16-26 years were included in the study. Hemodynamics was assessed by blood pressure (BP) office measurement and ambulatory monitoring, together with B-mode echocardiography data. Renal and renourinal structure and function was assessed by static and dynamic scintigraphy, renal ultrasound, renal radiography, excretory urography, color Doppler angiography of renal arteries, measurement of microalbuminuria in morning urine and glomerular filtration rate by endogenous creatinine. Plasma levels of uric acid, red blood cell ABO antigens, and Rhesus factor were also assessed to verify familial AH predisposition. AH was not an isolated pathology, being combined with various anomalies and disorders of kidneys, renal vessels, renourinary, cardiovascular, endocrine systems, as well as with metabolic disturbances and obesity. In more than 50% of the cases, renal anomalies were explained by genetic or intrauterine factors. The results obtained point to the importance of genetic and inherited renal anomalies' role in chronic AH syndrome development among young, call-up-aged men.